Abortion quality of care from the client perspective: a qualitative study in India and Kenya. Issue 9 (16th June 2021) - Baum, Sarah E; Wilkins, Rebecca; Wachira, Muthoni; Gupta, Deepesh; Dupte, Shamala; Ngugi, Peter; Makleff, Shelly
Abstract: Quality healthcare is a key part of people's right to health and dignity, yet access to high-quality care can be limited by legal, social and economic contexts. There is limited consensus on what domains constitute quality in abortion care and the opinions of people seeking abortion have little representation in current abortion quality measures. In this qualitative study, we conducted 45 interviews with abortion clients in Mumbai, India, and in Eldoret and Thika, Kenya, to assess experiences with abortion care, definitions of quality and priorities for high-quality abortion care. Among the many aspects of care that mattered to clients, the client–provider relationships emerged as essential. Clients prioritized being treated with kindness, respect and dignity; receiving information and counselling that was personalized to their individual situation and reassurance and support from their provider throughout the entire abortion process, including follow-up after the abortion. Many clients also noted the importance of skilled providers and appropriate care. There were similarities across the two country contexts, yet there were some differences in how clients defined high-quality care; therefore, specific political and cultural influences must be considered when implementing measurement and improving person-centred quality of care. These domains, particularly interpersonal interactions, should be prioritized in India and Kenya when health systems, facilities and providers design person-centred measures for quality in abortion care.